1995
DOI: 10.1016/1074-7613(95)90125-6
|View full text |Cite
|
Sign up to set email alerts
|

Loss of CTLA-4 leads to massive lymphoproliferation and fatal multiorgan tissue destruction, revealing a critical negative regulatory role of CTLA-4

Abstract: The B7-CD28/CTLA-4 costimulatory pathway can provide a signal pivotal for T cell activation. Signaling through this pathway is complex due to the presence of two B7 family members, B7-1 and B7-2, and two counterreceptors, CD28 and CTLA-4. Studies with anti-CTLA-4 monoclonal antibodies have suggested both positive and negative roles for CTLA-4 in T cell activation. To elucidate the in vivo function of CTLA-4, we generated CTLA-4-deficient mice. These mice rapidly develop lymphoproliferative disease with multior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
1,766
3
30

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,650 publications
(1,836 citation statements)
references
References 27 publications
37
1,766
3
30
Order By: Relevance
“…However, the increased numbers of CD4 1 FOXP3 1 T cells found in autoimmune inflammatory environments such as EAE or the rheumatoid joint [59][60][61] has been used to support the argument that Treg are expanded in inflammation but are unable to establish control [62]. Although defective CTLA-4 function and an expanded CD4 1 FOXP3 1 population in lupus patients may not be connected, there is a striking parallel found in CTLA-4-deficient mice [1,2]. It was originally noted that there is a marked increase in the number of CD4 1 CD25 1 T cells in mice lacking CTLA-4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the increased numbers of CD4 1 FOXP3 1 T cells found in autoimmune inflammatory environments such as EAE or the rheumatoid joint [59][60][61] has been used to support the argument that Treg are expanded in inflammation but are unable to establish control [62]. Although defective CTLA-4 function and an expanded CD4 1 FOXP3 1 population in lupus patients may not be connected, there is a striking parallel found in CTLA-4-deficient mice [1,2]. It was originally noted that there is a marked increase in the number of CD4 1 CD25 1 T cells in mice lacking CTLA-4.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of CTLA-4 in the down-modulation of immune responses is demonstrated in CTLA-4-deficient mice that develop a lethal lymphoproliferative syndrome with features of autoimmunity [1,2]. It is worth noting that by 3-5 wk, CTLA-4 -deficient mice suffer from a severe lupus-like autoimmune syndrome, which is more rapid in onset than other mouse models of systemic lupus erythematosus (SLE) [3].…”
Section: Introductionmentioning
confidence: 99%
“…CTLA-4 has a homologous structure to CD28 and binds to the same ligands, CD80/CD86, as CD28, but with much higher affinity. CTLA-4-deficient ( -/-) mice exhibit massive lymphoproliferative disorder and die at around 5 weeks of age [5,6]. It has been suggested that this lymphoproliferative disorder in CTLA-4 -/-mice is induced by polyclonal activation of peripheral T cells and that it is not due to a defect in the elimination of autoreactive T cells in the thymus [7][8][9][10], providing evidence for the in vivo function of CTLA-4 as a negative regulator of T cell responses [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…CTLA-4-deficient ( -/-) mice exhibit massive lymphoproliferative disorder and die at around 5 weeks of age [5,6]. It has been suggested that this lymphoproliferative disorder in CTLA-4 -/-mice is induced by polyclonal activation of peripheral T cells and that it is not due to a defect in the elimination of autoreactive T cells in the thymus [7][8][9][10], providing evidence for the in vivo function of CTLA-4 as a negative regulator of T cell responses [5,6]. However, the conclusion that CTLA-4 does not influence thymic selection was based mainly on the analyses of thymocyte development in TCR-transgenic (Tg) Â CTLA-4-deficient mice [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…CTLA-4 is structurally similar to CD28 and binds to CD80/86 with higher affinity than to CD28 (8), playing a crucial role in maintaining peripheral tolerance (9)(10)(11). Abatacept is a soluble fusion protein of the extracellular domain of CTLA-4 and the modified Fc portion of human IgG1 that eliminates complement activation (12,13).…”
mentioning
confidence: 99%